Testosterone replacement attenuates cognitive decline in testosterone-deprived lean rats, but not in obese rats, by mitigating brain oxidative stress - Hiranya Pintana (2018)
© 2015, American Aging Association. Testosterone replacement improves metabolic parameters and cognitive function in hypogonadism. However, the effects of testosterone therapy on cognition in obese condition with te stosterone deprivation have not been investigated. We hypothesized that testosterone replacement improves cognitive function in testosterone-deprived obese rats by restoring brain insulin sensitivity, brain mitochondrial function, and hippocampal synaptic plasticity. Thirty male Wistar rats had either a bilateral orchiectomy (ORX: O, n = 24) or a sham operation (S, n = 6). ORX rats were further divided into two groups fed with either a normal diet (NDO) or a high-fat diet (HFO) for 12 weeks. Then, ORX rats in each dietary group were divided into two subgroups (n = 6/subgroup) and were given either castor oil or testosterone (2 mg/kg/day, s.c.) for 4 weeks. At the end of this protocol, cognitive function, metabolic parameters, brain insulin sensitivity, hippocampal synaptic plasticity, and brain mitochondrial function were determined. We found that testosterone replacement increased peripheral insulin sensitivity, decreased circulation and brain oxidative stress levels, and attenuated brain mitochondrial ROS production in HFO rats. However, testosterone failed to restore hippocampal synaptic plasticity and cognitive function in HFO rats. In contrast, in NDO rats, testosterone decreased circulation and brain oxidative stress levels, attenuated brain mitochondrial ROS production, and restored hippocampal synaptic plasticity as well as cognitive function. These findings suggest that testosterone replacement improved peripheral insulin sensitivity and decreased oxidative stress levels, but failed to restore hippocampal synaptic plasticity and cognitive function in testosterone-deprived obese rats. However, it provided beneficial effects in reversing cognitive impairment in testosterone-deprived non-obese rats.